Effect of Use of Instructional Materials on Biology Student Cognitive Achievement in Biology in Lagos State Nigeria - Afariogun, Moses Sunday; Akintoye, Victor O. (Darul Yasin Al Sys, 2025)
This study examines the impact of instructional materials on Biology students’ cognitive achievement in Lagos State, Nigeria, using a quasi-experimental design with 140 SS1 students from public secondary schools. Results revealed that students taught with instructional materials (mean post-test score = 24.76) significantly outperformed those taught conventionally (mean = 18.51), with notable pre-test to post-test gains (11.19 vs. 10.54). Gender analysis showed no significant difference in achievement, underscoring universal efficacy. The findings affirm that instructional materials enhance engagement, comprehension, and retention, advocating their prioritized integration in science education to address resource gaps and improve academic outcomes. Stakeholders are urged to invest in teacher training and material provision to bolster Biology education in Nigerian schools.